Pengukuran Efisiensi Asuransi Syariah Dengan Data Envelopment Analysis (DEA) - Hulwah Tuffahati; Sepky Mardian; Edy Suprapto (Jurnal Akuntansi dan Keuangan Islam, 2016)
This research is aimed to measure the efficiency of Islamic Insurance Companies in Indonesia by using Data Envelopment Analysis (DEA). The sample used in this research are the Islamic Insurance Companies that publishes their full financial statements from the years 2012-2014. The variables in this study consists of two kinds of variables, namely input variables and output variables. The variable input is the total assets and the cost of commissions. While the variable output is the gross contribution and investment income. This study uses the intermediation approach with input orientation and use three types of measurements are the measurement of the efficiency of technical efficiency, pure technical and scale. The results of this study are in the groups of Islamic General Insurance Companies and Islamic Life Insurance Companies there are no company that achieve optimal efficiency levels in the three types of measurements.Whereas in the group Syariah General Insurance Unit are 2 companies optimally efficient in 3 measurements or by 28.57% of the total companies sampled in this group. And the group Syariah Life Insurance Unit are 4 companies optimally efficient in 3 measurements or 25% of total companies sampled in this group.